Prussian blue nanoparticles–mediated sensing and removal of 137Cs - Pandey, Prem C.; Yadav, Hari Prakash; Tiwari, Atul Kumar; Sawant, Shilpa N.; Sinharoy, Prithwish; Banerjee, Dayamoy; Narayan, Roger J. (Frontiers in Environmental Science, 2023)
Prussian blue nanoparticles with controlled nano-geometry were synthesized from the single precursor (potassium hexacyanoferrate) in the presence of three different reagents, Polyethyleneimine (PEI), tetrahydrofuran (THF)/H2O2, and 2-(3,4-Epoxycyclohexyl)-ethyl-trimethoxysilane (EETMS)/cyclohexanone which enabled the controlled nucleation and stabilization of PBNPs of variable plasmonic activity for selective sensing and removal of cesium radionuclides.The results of this study show sensing as well as removal of cesium ions based on the nano-geometry, magnetic behavior, and fluorescence quenching ability of Prussian blue nanoparticles as a function of the cesium ion concentration for the first time. A similar process was used to synthetically incorporate Prussian blue nanoparticles in mesoporous silica with potential use for the selective adsorption of 137 Cs, followed by the detection of radioactivity. The distribution coefficient (Kd) for adsorption of the cesium nuclide 137 Cs was calculated to be 3.2x10 4 ml/g -1 , displaying both Langmuir and Freundlich adsorption isotherms. The plasmonic activity of Prussian blue nanoparticles has enabled fluorometric sensing of cesium ions; regulating the spatial control between the functional Prussian blue nanoparticles and fluorescence probe molecule is a promising approach for Prussian blue nanoparticle enhanced fluorescence and fluorescence resonance energy transfer-based cesium ion sensing. Similarly, Prussian blue nanoparticles display superparamagnetic behavior; these magnetic properties were noted to be linearly dependent on the cesium ion concentration.